2005
DOI: 10.1084/jem.20041930
|View full text |Cite
|
Sign up to set email alerts
|

Type I interferon dependence of plasmacytoid dendritic cell activation and migration

Abstract: Differential expression of Toll-like receptor (TLR) by conventional dendritic cells (cDCs) and plasmacytoid DC (pDCs) has been suggested to influence the type of immune response induced by microbial pathogens. In this study we show that, in vivo, cDCs and pDCs are equally activated by TLR4, -7, and -9 ligands. Type I interferon (IFN) was important for pDC activation in vivo in response to all three TLR ligands, whereas cDCs required type I IFN signaling only for TLR9- and partially for TLR7-mediated activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
291
3
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(316 citation statements)
references
References 41 publications
21
291
3
1
Order By: Relevance
“…As such, we assume that pDC accumulation in lymphoid tissue represents the physiological correlate of the in vitro observed cluster formation, thereby providing the prerequisite for the positive type I IFN feedforward loop described here. This is in line with reports demonstrating that type I IFN activity is critical for murine pDC activation in vitro and in vivo [16,17], while pDCs are capable of an IFNAR-independent, early, yet weak IFN-α response [18]. However, it has also been noted that other studies have reported that pDCs do not require functional IFNAR signaling to exert type I IFN production themselves [19,20].…”
Section: Discussionsupporting
confidence: 91%
“…As such, we assume that pDC accumulation in lymphoid tissue represents the physiological correlate of the in vitro observed cluster formation, thereby providing the prerequisite for the positive type I IFN feedforward loop described here. This is in line with reports demonstrating that type I IFN activity is critical for murine pDC activation in vitro and in vivo [16,17], while pDCs are capable of an IFNAR-independent, early, yet weak IFN-α response [18]. However, it has also been noted that other studies have reported that pDCs do not require functional IFNAR signaling to exert type I IFN production themselves [19,20].…”
Section: Discussionsupporting
confidence: 91%
“…The in vivo relocalization of YFP ϩ cells from the red pulp via the marginal zone to the T cell area at Ϸ24 h after poly(I:C) stimulation is delayed, compared with the general redistribution of DCs after LPS treatment, where they are found in the splenic T cell zone by 6 h after injection (29). Interestingly, after injection of CpG ODN, YFP ϩ pDCs localized to the splenic T and B cell zones, whereas pDCs as a whole were described before to cluster mostly in the marginal zone with only few cells present in the splenic T cell areas (30). Taking these two independent observations into account, our data argue for a specialized migration pattern of IFN␤-expressing cells within the subpopulation of activated pDCs in response to activation with selective molecular patterns representative of different types of pathogens.…”
Section: Discussionmentioning
confidence: 88%
“…However, it has been reported that CCR7 expression is up-regulated on pDC in response to pathogenic stimuli, and that pDC migrate to the CCR7 ligands CCL19 and CCL21 expressed by stromal cells in the T cell zone and in HEV [29,50,51]. Moreover, TLR signals or type I IFN affect pDC migration via CXCR3L and CCR7 ligand induction [16,17]. Thus, IFN signaling in response to poly(I:C) stimulation might up-regulate these chemokine receptors on Ly49Q -pDC, allowing them to migrate into the periphery.…”
Section: Validation Of Pdc Conversion Into Cdcmentioning
confidence: 99%
“…Zuniga et al [15] recently showed that type I IFN negatively regulate pDC maturation during viral infection, and others [16] have reported that IFN control chemokine expression patterns that lead pDC to inflamed lymph nodes [17].…”
Section: Introductionmentioning
confidence: 99%